In the footsteps of prisoners of war from special NKVD camps in 1939-1940. Selected fifigures related to the Vilnius region - Kowalska, Ewa (Genocidas ir rezistencija, 2025)
The NKVD murder of the defenders of the Polish borders, in accordance with the decision of the Political Bureau of the Central Committee of the All-Union Communist Party of the Soviet Union of 5 March 1940, is still an open topic, full of secrets. Despite the passage of 85 years since the crime, many documents have not yet been handed over to the Polish side. First of all, there are no archives that would allow us to establish the names of all those murdered and indicate the location of the burials of all the victims. So far, the names of all those detained sent from the NKVD camps in Kozelsk, Starobelsk and Ostashkov for investigation, from which they did not return, and those whose lives were spared, have not been established either. In all these groups there were people of different nationalities, religions and professions. In Soviet documents, many inaccuracies concern people who are of Lithuanian nationality in various censuses. Despite the passage of time, we can only speak of traces of some of them, who were recorded in the statistics of camp records and among the survivors. It should be remembered that although it is important to determine the number of victims of the Soviet authorities’ policy, the most important thing is what was experienced, the fate of the citizens of the Second Polish Republic murdered in violation of all international laws and those few who were spared their lives, who remained under the supervision of the security services until the end of their days.